ANALYSIS OF THE EFFECTIVENESS OF SURABAYA REGIONAL REGULATION NO. 7 OF 2002 ON GREEN OPEN SPACE MANAGEMENT TOWARD VISITOR SATISFACTION AT KEBUN BIBIT WONOREJO - Rengga Puspita, Arum Hayu; Mumtaza, Naula; Rosita, Alifia Reza; Zahra, Tania Aulia; Agung, Magda Faradiba Mauludia (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2024)
This study aims to analyze the effectiveness of Surabaya City Regulation No. 7 of 2002 concerning Green Open Space (GOS) Management in relation to visitor satisfaction at the Wonorejo Seed Garden. Using a qualitative approach, data were collected through in-depth interviews, field observations, and documentation involving visitors, managers, and the Surabaya Environmental Agency. The results indicate that the regulation is relatively effective in enhancing the social, ecological, and educational functions of green open spaces. However, several challenges remain, including damaged facilities, limited maintenance, and low visitor awareness of park cleanliness. This study recommends periodic evaluations and improved coordination between local authorities and park managers to improve public satisfaction and green space governance.